Effects of Subjective Norm, Attitude and Consumer Desire Toward Intention to Purchase Indonesian Herbal - Wiwoho, Gunarso; Riptiono, Sulis (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Jamu is a traditional Indonesian medicinal beverage that has been a heritage product for generations. This research focuses on testing latent constructs used in empirical models to measure the intention of consumers to purchase Javanese Traditional Herbal Medicine Beverage, which is called Jamu or Indonesian herbal. This study involved 318 survey responses from society in Central Java, Indonesia. Data were collected using purposive sampling and analyzed using structural equation modeling (SEM) with AMOS. The results showed that two hypotheses were rejected of the six hypotheses tested there. Subjective norms are proven to positively affect consumer attitudes and desires but do not significantly to consumer purchase intention on Jamu. Furthermore, consumer attitude successfully contributed positively to increasing consumer desire but insignificant toward consumer purchase intention on Jamu. The other findings revealed that consumer attitude has the greatest role in increasing consumer desire, and consumer desires proved the best precursor of consumer intention to purchase Jamu. Keywords: subjective norm, attitude, intention, jamu, java